The Potential of Hydro Renewable Energy Technology to Electricity Remote Villages in Papua and Maluku Islands, Indonesia. Issue 1 (December 2021) - Sudibyo, H; Pikra, G; Fudholi, A
Abstract: The islands of Papua and Maluku are eastern Indonesia which consists of remote islands and villages. The Papua Islands consist of 3, 749 islands divided into two provinces, namely Papua and West Papua, while the Maluku Islands are 1, 735 islands into two provinces of Maluku and North Maluku, the number of inhabited islands in Papua and Maluku around 230 islands and around 100 newly electrified islands. The electrification ratio for Papua is 47.69%, West Papua is 89.94%, Maluku is 87.02% and North Maluku is 88.68%. The electrification ratio is still below the national average. Maluku Islands and Papua Indonesia has abundant renewable energy natural resources, namely hydro potential. The total hydro energy potential of Papua and Maluku is 808 MW. To overcome this shortage of electricity, it is necessary to develop a renewable energy generation system according to the potential of the area, namely hydro power. Energy generation technology that is environmentally friendly, efficient, effective, and reliable can be a solution for electrification in Papua and Maluku. Hydro power plants using vortex turbines, picohydro turbines and axial turbines for permanent magnet generators can be a solution to electrify areas or villages remote in Papua and Maluku.